2020
DOI: 10.1097/prs.0000000000006976
|View full text |Cite
|
Sign up to set email alerts
|

Neurotization of the Nipple-Areola Complex during Implant-Based Reconstruction: Evaluation of Early Sensation Recovery

Abstract: Summary: The concept of sensate autologous breast reconstruction is not novel, and prior literature has focused mainly on sensate abdominally based breast reconstruction. The goal of this article is to present the authors’ results with a novel technique performing sensate implant-based reconstruction. A database was prospectively maintained for patients who underwent implant-based sensate breast reconstruction. The anterior branch of the lateral fourth intercostal is identified and preserved during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…Twenty-three studies were found that met parameters for inclusion into this review. Of the studies included, seven looked primarily at DIEP flaps, 3,5-10 nine looked primarily at TRAM flaps, [11][12][13][14][15][16][17][18][19] two studies were novel implantbased studies, 20,21 and the remaining five studies dealt with other reconstructive modalities, including some where a technique was not specified. [22][23][24][25][26]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-three studies were found that met parameters for inclusion into this review. Of the studies included, seven looked primarily at DIEP flaps, 3,5-10 nine looked primarily at TRAM flaps, [11][12][13][14][15][16][17][18][19] two studies were novel implantbased studies, 20,21 and the remaining five studies dealt with other reconstructive modalities, including some where a technique was not specified. [22][23][24][25][26]…”
Section: Resultsmentioning
confidence: 99%
“…Supplemental Digital Content 3 is implant-based articles ( See table 3, Supplemental Digital Content 3 , which displays implant-based article methods. http://links.lww.com/PRSGO/C174) 20,21 and Supplemental Digital Content 4 is other included studies. 22–26 ( See table 4, Supplemental Digital Content 4, which displays other article methods.…”
Section: Methodsmentioning
confidence: 99%
“…Breast reinnervation for implant-based reconstruction has been described by several authors. 9 , 10 Our technique differs from current approaches in several ways. First, we aim to increase the donor axon-to-target density to maximize dermatome recovery by preserving all the nerves encountered during the mastectomy dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Intercostal-to-NAC interposition allografts employed during implant reconstruction to stimulate nerve regrowth and sensory recovery have recently been reported. 9 , 10 Peled and Peled 10 first described a novel technique in which following mastectomy, transected lateral intercostal nerves are dissected and coapted to 7 cm nerve allografts that are then secured to target subareolar nerves after implant reconstruction is complete. In their pilot study of 23 breasts, 67% reported similar preoperative and postoperative breast and NAC sensation.…”
Section: Introductionmentioning
confidence: 99%
“…The substantial drop in patient access also had a significant negative impact on the financial stability of these practices and especially private practices. 15 , 16 While patient access suddenly became practically nonexistent, the financial overhead many practices carry did not change. Plastic surgeons across the board reported that they were still required to pay rent, that they were not able to obtain any sort of negotiated discount for their rented equipment such as lasers and medical devices, and that there were no plans for pharmaceutical companies to take back any unused or expiring products.…”
Section: Discussionmentioning
confidence: 99%